Effect of administration routes on the efficacy of human umbilical cord mesenchymal stem cells in type 2 diabetic rats - Tao, Qiqiang; Wu, Youzhi; Pang, Huiwen; Lv, Pinglei; Li, Wenrui; Nie, Xuqiang; Han, Felicity Y. (Frontiers in Endocrinology, 2025)
BackgroundHuman umbilical cord mesenchymal stem cells (UCMSCs) are being investigated in various clinical trials for different conditions, including type 2 diabetes mellitus (T2DM). However, there is limited research on the optimal injection routes for UCMSCs in T2DM, particularly intravenous injection.ObjectiveThe objective of this study aims to investigate the efficacy of four different administration routes of UCMSCs in treating T2DM rats, including pancreas injection (DP), tail vein injection (DT), intraperitoneal injection (DI), and dorsal pancreatic artery injection (DPA).ResultsAfter two weeks of UCMSCs treatment, the fasting blood glucose levels in the DT group decreased significantly. The oral glucose tolerance test (OGTT) levels and the islet structure in the DT group almost recovered to normal. The contents of C-P and GLP-1 in serum increased significantly in all treatment groups, while the levels of INS, TNF-α, IL-6, IL-1β, IAA, and GSP decreased significantly. These improvements were further observed after four weeks of UCMSCs treatment. Histological analysis confirmed the progression of pancreatic recovery in all treatment groups, with the DT group showing the most significant improvement, correlating with the observed efficacy. Immunohistochemistry results further demonstrated increased insulin and PDX-1 expression, along with reduced glucagon levels in UCMSCs-treated rats. Additionally, liver and kidney function significantly improved across all treatment groups, with the DT group showing the best outcomes.ConclusionOverall, these findings suggest that the administration route significantly affected the efficacy of UCMSCs in treating T2DM, with tail vein injection showing the most effective results.